Particles of echovirus 18 open to release their genomes in vivo - Liya Mukhamedova; David Buchta; Zuzana Trebichalská; Yevgen Levdansky; Jana Moravcová; David Potěšil; Zbyněk Zdráhal; Dominik Hrebík; Lucie Nepovímová; Torleif Tollefsrud Gjølberg; Jan Terje Andersen; Jiří Nováček; et al. (Proceedings of the National Academy of Sciences, 2026)
Enteroviruses cause a broad spectrum of human diseases, ranging from mild respiratory or gastrointestinal infections to severe neurological disorders such as aseptic meningitis and encephalitis. Enterovirus cell entry involves receptor-mediated endocytosis followed by destabilizing rearrangements of the virus capsid that enable genome release. However, the mechanism of enterovirus genome release has not been visualized in infected cells. Here, we used cryoelectron tomography and microscopy to image echovirus 18 (E18) entry into host cells and its interaction with the neonatal Fc receptor (FcRn). 30 min postinfection, endosomes and cytoplasm contained empty capsids missing one or several pentamers of capsid proteins, providing evidence that in vivo E18 releases its genome through capsid opening. In vitro, FcRn binding induced the expulsion of pocket factors from hydrophobic pockets in VP1, priming the virus for uncoating. The cryoelectron microscopy reconstruction of genome-containing particles of E18 inside infected cells did not reveal pocket factors, indicating that receptor binding triggers the same priming process during infection. We did not detect activated particles in infected cells, suggesting that these intermediates are short-lived and rapidly release their genomes in vivo. Our results identify capsid opening as the in vivo mechanism of echovirus 18 genome release, providing structural evidence for a process previously only inferred from in vitro experiments.